Using Project-Based Learning to Foster Mathematics Creative Thinking and Problem-Solving Skills of Elementary School Students - Sabina Ndiung; Sebastianus Menggo (Jurnal Pendidikan Progresif, 2024)
Using Project-Based Learning to Foster Mathematics Creative Thinking and Problem-Solving Skills of Elementary School Students. Objectives: This research aims to describe creative thinking skills and mathematical problem-solving abilities by implementing the Project-Based Learning model. Methods: This research used a quasi-experimental approach with a posttest-only control group design. The research was conducted at the Mano I of Catholic Elementary School during the odd semester of the 2023/2024 academic year. The research sample involved 53 fifth-grade students selected using random sampling techniques. The data collection instrument employs a descriptive test consisting of five questions each to assess creative thinking skills and problem-solving abilities. These instruments have undergone testing and have demonstrated reliability coefficients of 0.84 and 0.81, within the high category. The data collection method used in this research uses a test technique on fraction material, which consists of 10 questions with details of 5 creative thinking skills test items and 5 problem-solving ability test items. The instruments in this research are test questions, divided into creative thinking skills tests and problem-solving ability tests, each of which uses high-level thinking indicators, classified into C4 and C5 questions. The rubric for assessing creative thinking skills and problem-solving abilities is used in this research as a basis for consideration when assigning grades. The data analysis employed the Multivariate Analysis of Variance (MANOVA) test technique using the Statistical Package for Social Sciences (SPSS) version 23.0 program for Windows. Before this, several assumption tests were conducted, including tests for normality of data distribution, homogeneity of variances, and multicollinearity. Findings: Simultaneously, students taught utilizing project-based learning demonstrate higher creative thinking and problem-solving skills than those taught using conventional methods. The PjBL model significantly impacts elementary school students' creative thinking and mathematics problem-solving skills. Conclusion: The PjBL approach is an acceptable choice for educators to foster creativity. Keywords: creative thinking skills, problem solving mathematics, project-based learning.DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202453